2022
DOI: 10.7759/cureus.29183
|View full text |Cite
|
Sign up to set email alerts
|

Renal Dysfunction in Pediatric Patients in Iraq With β-Thalassemia Major and Intermedia

Abstract: BackgroundWith optimum transfusion and chelation therapy, the survival of β-thalassemia patients and the incidence of various complications, including renal complications, have improved. ObjectivesTo investigate renal involvement in β-thalassemia patients using serum and urinary biochemical markers of glomerular and tubular dysfunction. MethodsThis case-control study included 69 β-thalassemia major (β-TM) patients, 23 β-thalassemia intermedia (β-TI) patients, and 100 healthy controls, all ranging from 1 to 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This reactive iron has the potential to trigger the generation of reactive oxygen species (ROS) and cause cellular damage. Consequently, there may be a defect in reabsorption, leading to increased urinary potassium excretion [32]. It is important to note that our study contradicts the findings, which reported a significant increase in serum potassium levels [37,38].…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…This reactive iron has the potential to trigger the generation of reactive oxygen species (ROS) and cause cellular damage. Consequently, there may be a defect in reabsorption, leading to increased urinary potassium excretion [32]. It is important to note that our study contradicts the findings, which reported a significant increase in serum potassium levels [37,38].…”
Section: Discussioncontrasting
confidence: 94%
“…Our study's results indicate a significant decrease in serum potassium, although it remains within the normal range (P ≤ 0.05). These findings confirm previous research, including studies on thalassemia patients [30,32]. The decrease in serum potassium levels could be attributed to the fact that most potassium is reabsorbed in the loop of Henle and proximal tubule.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In previous studies by Aldudak et al (2) and Mohkam et al (14) on patients receiving DFO using common markers, early renal changes could not be demonstrated. As a result of chronic anemia, iron deposition, and/or drug like DFO cumulative toxicity, these studies have primarily shown the presence of proximal tubular compromise in those patients (2,14) . Papassotiriou et al (15) also reported slight changes of cystatin C level during deferasirox treatment in βthalassemia population.…”
Section: Urinary β2-mg (Mg/l) Discussionmentioning
confidence: 88%
“…Thalassemia patients may experience renal dysfunction as of DFO side effects, iron deposition in the kidney, or other causes such as lipid peroxidation, stress oxidation, generation of free radicals, and thrombosis (2,3) release free radicals and thrombosis (3) .…”
Section: Introductionmentioning
confidence: 99%